Are We There Yet? A Legal Assessment And Review Of The Concept Of Sustainable Development Under International Law - Pavlovskaia, Evgenia (Journal of Sustainable Development Law and Policy, 2025)
Some of the most consistently utilized terms in international environmental law are “sustainable development” and “sustainability”. Sustainable development is mentioned in virtually every domestic, regional and international laws on environment, energy and natural resources. This has led to the contentions by some scholars that the concept of sustainable development has matured into customary international law, or at least has become a general principle of international environmental law. Many researchers, however, argue that the idea of sustainable development is vague, elusive and does not add much to the efficient implementation of international environmental law. This article aims to examine and discuss these views. In this paper, the content of the widely used concepts “sustainability” and “sustainable development” are studied from the perspective of their implementation in different parts of the world. The article examines the status of the concept of sustainable development under international law, its implementation across sectors, its key contributions to international law and how its practical actualization can be further strengthened. The article sets out with a broad inter-disciplinary review of the existing definitions of the concepts “sustainability” and “sustainable development”. The article will then examine examples of how “sustainability” and “sustainable development” are incorporated in contemporary environmental law, in order to highlight its current status under international law and its overall influence on different spheres of our life. Major difficulties and challenges associated with implementing and enforcing sustainability are also examined. It is suggested that market systems should be supplemented by political processes and legal regulations that include special mechanisms and tools to protect and control the health of the environment. Growing awareness of sustainability, primarily environmental, among produces is viewed in the article as a very positive trend. It is welcomed that more and more industries are engaged in sustainable production throughout the entire product life cycle. The use of such tools as sustainability criteria, sustainability standards and eco-labels must also be promoted.